Synthesis of Transition Metal Complexes of Isoniazid Derivatives and Urease Inhibition Activity Detection - Zhang, Yi-Heng; Fang, Ze-Yu; Sun, Juan; Wu, Yuan-Feng (Indian Journal of Pharmaceutical Education and Research, 2022)
It have been reported that the transition metal complex of Schiff base ligands have the ability to inhibit urease. Herein, in this manuscript, two novel transition metal complexes [Cd2(L)2·(H2O)] (1), [Pb(L)·, [Pbe2) were synthesized based on chelating hydrazone ligand N‘-(pyridin-2-ylmethylene)isonicotinohydrazide (L). These compounds were tested by single crystal X-ray diffraction and determined by structure and tested for urease resistance in vitro. The complex 2 exhibited better the activities of inhibiting than the positive control acetohydroxamic acid with an IC50 =2.5 μM, while the complex 1 showed weak activity, and complex 2 acted as an effective urease inhibitor.
Keywords: Cadmium(II) complexes; Plumbum(II) complexes; Crystal structure; Schiff; base; Urease inhibitor